Cardiac troponin T is elevated and increases longitudinally in ALS patients. Issue 1 (2nd January 2022) - Kläppe, Ulf; Chamoun, Sanharib; Shen, Qing; Finn, Anja; Evertsson, Björn; Zetterberg, Henrik; Blennow, Kaj; Press, Rayomand; Samuelsson, Kristin; Månberg, Anna; Fang, Fang; Ingre, Caroline
Abstract: Objective: To test whether high-sensitivity cardiac troponin T (hs-cTnT) could act as a diagnostic or prognostic biomarker in ALS, comparing hs-cTnT to neurofilament light (NfL). Methods: We performed a case-control study, including 150 ALS patients, 28 ALS mimics, and 108 healthy controls, and a follow-up study of the ALS patients, during 2014–2020 in Stockholm, Sweden. We compared concentrations of hs-cTnT in plasma and NfL in the cerebrospinal fluid between cases and controls. To evaluate the diagnostic performance, we calculated the area under the curve (AUC). Hazard ratios (HRs) were estimated from Cox models to assess associations between hs-cTnT and NfL at ALS diagnosis and risk of death. The longitudinal analysis measured changes of hs-cTnT and NfL since ALS diagnosis. Results: We noted higher levels of hs-cTnT in ALS patients (median: 16.5 ng/L) than in ALS mimics (11 ng/L) and healthy controls (6 ng/L). Both hs-cTnT and NfL could distinguish ALS patients from ALS mimics, with higher AUC noted for NfL (AUC 0.88; 95%CI 0.79–0.97). Disease progression correlated weakly with hs-cTnT (Pearson's r = 0.18, p = 0.04) and moderately with NfL (Pearson's r = 0.41, p < 0.001). Shorter survival was associated with higher levels of NfL at diagnosis (HR 1.08, 95%CI 1.04–1.11), but not hs-cTnT. hs-cTnT increased (12.61 ng/L per year, 95%CI 7.14–18.06) whereas NfL decreased longitudinally since ALS diagnosis. Conclusions: NfL is a stronger diagnostic and prognostic biomarker than hs-cTnT for ALS. However, hs-cTnT might constitute a disease progression biomarker as it increases longitudinally. The underlying causes for this increase need to be investigated.